1981
DOI: 10.2134/jeq1981.00472425001000040010x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Field‐Grown Soybeans Exposed to Acid Rain and Sulfur Dioxide Alone and in Combination

Abstract: Sulfur dioxide (SO2)‐fumigated and unfumigated field plots of soybeans (Glycine max cv. Wells) were exposed to acid (pH 3.1) or control (pH ∼ 5.3) precipitation simulants to determine effects on growth and productivity. The precipitation simulants were applied at approximately 5‐day intervals in July and August with a total of 3.4 cm applied in 1977 and 4.5 cm in 1978. Sulfur dioxide fumigations of ∼ 4‐hour durations were performed 24 times in 1977 and 17 times in 1978, resulting in an average fumigation conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Significant reductions in yield of soybean were also found by Banwart and co-workers using a comparable experimental procedure (Banwart, Hassett & Vasalis, 1984). However, in other field experiments with this species, acid rain treatments did not cause significant reductions in yield (Irving & Miller, 1981;Troiano et al, 1983 ;Heagle et al, 1983). Differences in response to simulated acid rain have also been recorded in experiments with other crop species (Lee et al, 1981;see Irving, 1983).…”
Section: Introductionmentioning
confidence: 59%
“…Significant reductions in yield of soybean were also found by Banwart and co-workers using a comparable experimental procedure (Banwart, Hassett & Vasalis, 1984). However, in other field experiments with this species, acid rain treatments did not cause significant reductions in yield (Irving & Miller, 1981;Troiano et al, 1983 ;Heagle et al, 1983). Differences in response to simulated acid rain have also been recorded in experiments with other crop species (Lee et al, 1981;see Irving, 1983).…”
Section: Introductionmentioning
confidence: 59%
“…Depressions of photosynthetic rates may occur within minutes to hours after the initiation of exposure, are often reversible, and may not be accompanied by major visible injury, at least at low concentrations (Black and Unsworth, 1979). Recurrent exposure to low concentrations may cause the destruction of chlorophyll and hasten leaf senescence (Irving and Miller, 1981). At higher concentrations, responses often are not reversible and often are associated with the appearance of visible injury.…”
Section: Photosynthesis-s02mentioning
confidence: 99%
“…Terrestrial ecosystems are undergoing simultaneous changes in climate and biogeochemical cycles, and those changes could affect plant net primary production (NPP) positively or negatively. Changes such as elevated CO 2 , nitrogen deposition (Xia and Wan, 2008) and temperature increases (Raich et al, 2006) were found to enhance plant productivity, whereas elevated O 3 (Liu et al, 2005), drought (Zhao and Running, 2010) and acid deposition (Irving and Miller, 1981) generally decreased productivity. These changes in primary production could alter both the quality and quantity of above-ground litter inputs to soil (Liu…”
Section: Introductionmentioning
confidence: 98%